Compacted fly ash mixtures as highway safety barriers - Mehmetoğlu, Doruk. (Thesis (M.S.)- Bogazici University. Institute for Graduate Studies in Science and Engineering, 1994., 1994)
During the past years, research had been carried on in the Bogaziçi University, Soil Mechanics and Foundation Engineering Laboratory to find a way of utilizing two wastes, namely fly ash and rubber chips from old tires. As a result, it had been determined that these wastes could successfully be used in waste liner construction. The purpose of this work is to find a new field of utilization for these materials. The materials used for this purpose are self cementitious high-calcium fly ash from Soma TEK-B Thermal Power Plant, pulverized waste rubber, lime and spherical and crushed ice particles. As a result of the work undertakan a light-weight energy absorbing material which may be utilized in the construction of traffic barriers is developed and a new field of utilization for fly ash and waste rubber is provided. For the laboratory experiments, a total number of 126 fly ash-rubber-ice and fly ash-lime-ice samples of different compositions were prepared using static compaction. Additional water in the form of crushed or spherical ice particles was provided for the hydration reaction of fly ash and to increase the energy absorbing capacity by introducing voids into the samples. All of the samples were cured for a period of 56 days. Ultra sound, compression and double punch tests were performed on them. Laboratory studies indicated a maximum increase in compressive strength with added lime and crushed ice. Energy absorbing capacity and tensile strength were increased most after adding lime and spherical ice. It was concluded that this material could be used in crash-cushion construction.
Keywords: Fly ash.; Waste product.; Rubber, Reclaimed.